2005
DOI: 10.1080/00016480510003192
|View full text |Cite
|
Sign up to set email alerts
|

Motion sickness susceptibility associated with visually induced postural instability and cardiac autonomic responses in healthy subjects

Abstract: In subjects with a low susceptibility to motion sickness as rated using a standardized questionnaire, there was no significant effect of visual stimulus on postural sway or HRV at any frequency of motion. Subjects with a high susceptibility to motion sickness showed significant postural instability induced by visual stimuli (p < 0.01). Visual stimuli presented at a frequency of 0.1 Hz significantly increased the low-frequency power (LF) of HRV, decreased the high-frequency power (HF) of HRV and increased the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 17 publications
3
55
0
Order By: Relevance
“…The influence of video-induced motion sickness on the body has been measured by employing subjective scales such as the simulator sickness questionnaire (SSQ) (Kennedy et al, 1993). Further, it is also measured by quantitatively investigating the relationship between external factors and internal conditions using physiological indices such as respiratory functions, electrocardiograms, skin electrical activity, fluctuation of the center of gravity, and electrogastrograms (Holomes and Griffin, 2001;Himi et al, 2004;Yokota et al, 2005). By using the SSQ and stabilometry (body sway), we examined whether the VIMS was induced by a stereoscopic movie in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of video-induced motion sickness on the body has been measured by employing subjective scales such as the simulator sickness questionnaire (SSQ) (Kennedy et al, 1993). Further, it is also measured by quantitatively investigating the relationship between external factors and internal conditions using physiological indices such as respiratory functions, electrocardiograms, skin electrical activity, fluctuation of the center of gravity, and electrogastrograms (Holomes and Griffin, 2001;Himi et al, 2004;Yokota et al, 2005). By using the SSQ and stabilometry (body sway), we examined whether the VIMS was induced by a stereoscopic movie in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, HR, SCL, Resp, LF power and LF/HF ratio were expected to increase with time and/or with increasing motion sickness, whereas Temp and BVP were expected to decrease [12,14,24,[27][28][29][30][31][32]. Particularly surprising was the decrease in respiration rate over time and with increasing motion sickness, which contradicts previous research where slow breathing has been shown to [33,34].…”
Section: Psychophysiologymentioning
confidence: 97%
“…It has been observed that people susceptible to motion sickness also show more postural instability (Cobb, 1999;Faugloire et al, 2007;Fukuda, 1975;Smart et al, 1998;Takahashi et al, 1992;Van Emmerik et al, 2005;Yokota et al, 2005). Yet, negative or lacking correlations have been observed too (Reed-Jones et al, 2008;Stoffregen et al, 2008;Warwick-Evans et al, 1991;Golding et al, 2009).…”
Section: Posturementioning
confidence: 99%